PENGEMBANGAN MEDIA PUBG UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Nur Laili Fitriyah; Tety Nur Cholifah (STKIP Persada Khatulistiwa Sintang, 2020)
This study aims to: (1) developing pictorial Pop-Up media (PUBG) appropriately to improve learning outcomes of elementary school students, (2) student learning outcomes using Picture Pop-Up media (PUBG). The research used is Research and Development (R&D) Borg and Gall. The subjects studied were students of grade IV SD. Instrument there are 5 data collection, namely: observation, interviews, questionnaire sheets, tests written, and documentation. Observations were made at SD Negeri 02 Glanggang. Interviews were conducted with class IV homeroom teachers. Questionnaire sheet respondents there are 2 lecturers for media validation and the fourth grade homeroom teacher for SD material validation. Instrument given pretest and posttest. Media developing is feasible or not seen from the results of material validation and media. The results of material validation were obtained 98% and media validation was obtained 94% which is categorized as very valid. On student learning outcomes seen from the pretest obtained the highest score therefore, it’s categorized as sufficient. In the posttest, the highest score was 98 and lowest is 86, the mean value is 93.5 which is categorized as very good. Based on the difference between the pretest and posttest mean scores the difference is obtained 45.4